Application of Student Work Sheet Based on Scientific in Training Science Process Skills in Science Learning Class V At State Elementary School 4 Gulang Mejobo Kudus - Shofa, Firsya Maurna; Hanik, Elya Umi (International Research-Based Education Journal, 2023)
This study aims to determine the application of scientific-based student worksheets (LKPD) at SDN 4 Gulang Mejobo Kudus. The success of the implementation, as well as anything f supporting and inhibiting actors in the application of the worksheet. This study uses a type of field research with a qualitative approach. Data collection techniques applied are through observation and interviews, as well as through documentation. The results of the research show: First, the Application of Scientific-Based Student Worksheets (LKPD) in Training Science Process Skills in Class V Science Learning at SDN 4 Gulang Mejobo Kudus, there are 3 stages, namely planning. Implementation, and evaluation. Second, the successful application of scientific-based student worksheets (LKPD) in training science process skills in fifth-grade science learning at SDN 4 Gulang Mejobo Kudus creates an active class, students are eager to observe material, group objects related to the material, taking measurements. Students become confident in communicating the results of their work and can make conclusions from the results of their learning. Third, Factor in the application of scientific-based student worksheets in science learning class V at SDN 4 Gulang Mejobo Kudus namely supporting factors which include good school management, guaranteed teacher professionalism, adequate learning resources, varied learning methods, and media, there is an interest in learning and learning competition between students. And the inhibiting factors include inadequate infrastructure, parental support for poor student learning outcomes, and students' learning mental readiness that is not the same.